Winning at human relations : how to keep from victimizing yourself - Chapman, Elwood N. (Crisp Pub. Menlo ParkUS, 1989)
Identifies factors which damage human relations on the job, for example, insensitivity, negative attitude, absenteeism; and factors which enhance relations, for example, positive attitude and communication. Explains how to repair damaged work relationships, especially with a supervisor. Shows how victimization occurs, how it affects one's career, and how to avoid being victimized. Provides 10 techniques for maintaining healthy relationships.